The Tsallis Entropy as a Social Entropy - Nieto-Chaupis, Huber (2019)
We analyze social disorder using the Tsallis entropy that is characterized by having the pseudo-additivity property and being this used to feature certain dynamical systems in nature. By taking advantage of this property, we apply this entropy to social systems that are showing chaotic behavior due to the conjugation of one or more anomalies. When these anomalies are efficiently identified, the Tsallis entropy can be used as a software inside of a smart city program that do protect population against of imminent social risk. In a prospective Internet of Things, this physics-mathematical methodology would provide advantages as to anticipate events against the wellness of a concrete human group containing vulnerable population.